Abnormal blood pressure response to exercise and ventricular arrhythmias: a suspicious association in athletes - Di Gioia, G.; Ferrera, A.; Maestrini, V.; Monosilio, S.; Squeo, M. R.; Lemme, E.; Serdoz, A.; Mango, F.; Pelliccia, A. (Journal of Hypertension, 2024)
Introduction: Abnormal blood pressure response to exercise (ABPR) in athletes is considered a risk for incident hypertension, conferring a higher cardiovascular risk profile. We sought to describe the clinical cardiovascular features of athletes with ABPR and, moreover, the relationship of ABPR with occurrence of exercise-induced ventricular ectopic beats (VEBs).